Ajaran yang Sehat: Merajut Kewajiban Keluarga Kristen berdasarkan Tafsir Sosio-Retorika Titus 2:1-10 - Daniel Rizki Purba (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2024)
The article explores the socio-rhetorical interpretation of Titus 2:1-10, focusing on the Christian family's obligations. Titus, one of the Pastoral Epistles, addresses issues within the church community. With its distinctive language style and historical background, Titus offers advice to church leaders and addresses the challenges faced in Crete. Through socio-rhetorical analysis, the study delves into the inner texture and intertexture of the text, examining the implied author, narrator, and characters' roles in conveying the message. The text emphasizes the importance of personal conduct aligned with sound teaching, particularly within the family structure. Titus advocates for healthy relationships and behavior within households, influencing broader community dynamics. Employing qualitative research methods, the study integrates socio-cultural contexts to elucidate the text's message. Ultimately, Titus 2:1-10 serves as a rhetorical strategy urging adherence to sound doctrine, with the family serving as the foundational unit for moral education and behavior. Upholding these teachings fosters a community characterized by authenticity and virtue, essential for every individual within the family unit.